Current Progress in Breast Implant-Associated Anaplastic Large Cell Lymphoma - Wang, Yichen; Zhang, Qi; Tan, Yufang; Lv, Wenchang; Zhao, Chongru; Xiong, Mingchen; Hou, Kai; Wu, Min; Ren, Yuping; Zeng, Ning; Wu, Yiping (Frontiers in Oncology, 2022)
Breast implant-associated anaplastic large-cell lymphoma (BIA-ALCL) is an uncommon type of T-cell lymphoma. Although with a low incidence, the epidemiological data raised the biosafety and health concerns of breast reconstruction and breast augmentation for BIA-ALCL. Emerging evidence confirms that genetic features, bacterial contamination, chronic inflammation, and textured breast implant are the relevant factors leading to the development of BIA-ALCL. Almost all reported cases with a medical history involve breast implants with a textured surface, which reflects the role of implant surface characteristics in BIA-ALCL. With this review, we expect to highlight the most significant features on etiology, pathogenesis, diagnosis, and therapy of BIA-ALCL, as well as we review the physical characteristics of breast implants and their potential pathogenic effect and hopefully provide a foundation for optimal choice of type of implant with minimal morbidity.